A New Gloria for Satie's Messe des pauvres - Schwandt, Erich (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1998)
Erik Satie worked on his Messe des pauvres from 1893 to 1895 but never completed it. After Satie's death, Darius Milhaud selected movements from the composer's notebooks and published them in 1929 as the Messe des pauvres for organ and voices. The Mass is missing its Gloria; however, the only contemporary account suggests that the Gloria was in existence in 1895. The object of this article is to propose a new Gloria based on one of Satie's contemporaneous piano préludes. As well, to involve the singers more fully, two very short movements are furnished with Latin texts.